Depressor consonants in Geji - (:unkn) unknown (My University, 2008)
Geji, a language spoken in Bauchi State (Northern Nigeria) belonging to the the West-B3 group of Chadic languages, has a tonal system based on a three-level distinction between Hi, Mid and Low, with Falling and Rising combinations of Hi and Lo. This system is fully operational in both grammar and lexicon, but it may be the result of the interaction between a set of voiced consonants called depressor consonants and a deeper two-level opposition between Hi and non-Hi tones. However, the effect of depressor consonants in Geji is limited to the lexical phonology of stock Geji vocabulary: they don't apply to words recently borrowed from Hausa or to ideophones; they don't apply to postlexical phonology, as they don't block the rightward spreading of H tone. Geji now operates a 3-tone system where Hi tone is marked, i.e. it is the most active in terms of spreading, and Mid tone is unmarked, i.e. it is totally ineffective in the rules of tone spreading.
Keywords: African Research